Microstructure and Phase Composition of Porous SiC-Ceramic Obtained by Spark Plasma Sintering of Preceramic Paper; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 17 - Sedanova E. P. Elizaveta Pavlovna (2023, 2023)
Title screen